ETHYLENE COPOLYMER WITH IMPROVED ELASTICITY AND PROCESSIBILITY - JUNG, HYUN WOOK; OH, SE WON; KWON, SEUNG BUM; HAM, HYEONG TAEK; CHAE, SUNG SEOK (2012)
Provided is an ethylene copolymer with improved elasticity and processibility. More specifically, provided is an ethylene copolymer which exhibits a high zero shear viscosity and a large degree of shear thinning degree, and shows rheological characteristics behaviors differentiated from products manufactured by using the existing metallocene and Ziegler-Natta catalysts. In addition, provided is an ethylene copolymer which has a low processing load, shows differentiated behavior in Van-Gurp Palmen analysis, and exhibits excellent Neck-in characteristics. L'invention concerne un copolymère de l'éthylène ayant une élasticité améliorée et une aptitude améliorée à la mise en oeuvre. Plus particulièrement, l'invention concerne un copolymère de l'éthylène qui présente une viscosité de cisaillement zéro élevée et un important degré de fluidisation par cisaillement, et présente des comportements de caractéristiques rhéologiques qui se différencient des produits fabriqués à l'aide des catalyseurs métallocènes et Ziegler-Natta existants. En outre, l'invention concerne un copolymère de l'éthylène qui a une faible charge de traitement, présente un comportement différencié dans une analyse de Van-Gurp Palmen et présente d'excellentes caractéristiques de rétraction.